La crisis de la filoxera en España según la representación diplomática francesa - Molleví Bortolo, Gemma; Serrano Gine, David (Geographicalia, 2014)
During the last quarter of the XIXth century, the French diplomacy did different reports about the situation of the grapevine in Spain. The information explained the pest of the phylloxera in the vineyards and her different aspects: the advance of the disease, the social and economic techniques of control or her agrarian consequences. These reports were centered in the French regions, but also included references to other countries. The information concerning to the situation of this disease in Spain is diverse and irregular, although it represent an interest tool for study the plague of the phylloxera in Spain. It is important to know that the phylloxera question has been studied largely. For this reason, this information must be understood like a complement for the other studies realised in the agrarian history of the grapevine.
Keywords: phylloxera; grape-vine; agrarian crisis; French diplomacy